Botanical composition and models of metabolizable energy availability from undergrowth in oil palm plantations for ruminant production - Dahlan, I.; Yamada, Y.; Mahyuddin, M.D. (Kluwer Academic Publishers, 1993)
The availability of undergrowth is essential for integrating ruminant animals into oil palm plantations. This is because undergrowth can be used as a feed resource for ruminants. This type of production system has the advantage of diversifying income and controlling weeds in the plantation. At least fve botanical groups of herbage can be found in oil palm plantations, namely, grasses, broad leaved plants, legumes, ferns and palms. Grasses were found in abundant through all palm ages. Most grasses are tolerant to higher light intensity and some are shade-tolerant. This study showed that in the early stages of oil palm crop development, sun-loving species tend to dominate the field, mostly broad leaves and legumes, but they will gradually be replaced by shade-tolerant plants when the canopies close. Concentration of metabolizable energy in herbage on offer was 4.6 to 7.0 MJ/kg dry matter. Crude protein content of grasses, broad leaves, legumes, ferns and palms are 11.5%, 15.4%, 16.3%, 12.5% and 12.0%, respectively. Ruminant animals preferred broad leaved plants more than other botanical groups found in oil palm plantation. This paper showed that metabolizable energy available (MEA) models can be used for predicting available energy (MJ/ha/day) from the system for grazing ruminants. This is because MEA model was developed based on both quality and quantity of herbage present in the ecosystem. © 1993 Kluwer Academic Publishers.